Analysis Of The Need For Interactive Multimedia Development Based On Inquiry Training On Science Learning In The Pandemic Period - Hasanah, Uswatun; Yufiarti, Yufiarti; Astra, I Made; Sumantri, Mohamad Syarif (Jurnal Basicedu, 2021)
This study aims to analyze students' needs for inquiry-based interactive multimedia in science learning during the pandemic. The research subjects were 125 elementary school students in Setiabudi District who were selected by random sampling. Data were collected using semi-structured interview techniques and questionnaires to several teachers and students. The results of semi-structured interviews show that there are limitations to the media that teachers provide to students in science learning during this pandemic. The results of the questionnaire analysis of student needs show that 1) the teaching media needed by students is interactive multimedia and 2) the material needed by students is the digestive and respiratory systems in humans, as well as the reproductive and circulatory systems in humans.